DEVELOPMENT OF BATIK ORNAMENTAL MOTIFS THROUGH THE LEGEND OF RAWAPENING LAKE - Ridha Sarwono; Ardyansyah Nur Syarif Hidayatullah (Proceeding of the International Conference on Mathematical Sciences, Natural Sciences, and Computing, 2024)
: This research aims to develop batik ornamental motifs inspired by the legend of Rawapening Lake, a folklore from Central Java. Through a qualitative-descriptive approach, this research identifies key elements of the legend that can be applied in batik motif design. Data were collected through in-depth interviews with batik artisans and cultural experts as well as related literature studies. The results show that ornamental motifs developed from the elements of the legend of Lake Rawapening not only enrich the variety of batik motifs, but also have the potential to enhance local cultural appreciation and the creative economy in the area.